Atrial Fibrillation Cycle Length and Atrial Size in Horses with and without Recurrence of Atrial Fibrillation after Electrical Cardioversion. (24th February 2014) - De Clercq, D.; Decloedt, A.; Sys, S.U.; Verheyen, T.; Van Der Vekens, N.; van, G.
<x xml:space="preserve">Abstract</x> Background Atrial fibrillation (AF) cycle length (CL) and atrial size have been used in humans to characterize electrical and structural remodeling to predict outcome of cardioversion of AF and risk for AF recurrence (rAF). Hypothesis Atrial fibrillation cycle length can be determined in horses with AF, and AFCL and atrial size are related to risk for rAF. Animals Eighteen horses with naturally occurring AF that were successfully converted to sinus rhythm (SR) by transvenous electrical cardioversion (TVEC). Methods Prospective study. Horses with severe valvular regurgitation, left atrial enlargement, or that required sedation for catheter placement were excluded. In all horses intra‐atrial electrograms were recorded and estimated AF duration and echocardiographic parameters were determined before TVEC. The follow‐up time was 1 year after TVEC. Results Atrial fibrillation cycle length could be determined in all horses. The AFCL and the shortest 5th percentile (p5) AFCL in horses with rAF (n = 6 or 33%) were (mean ± SD) 157 ± 28 and 134 ± 24 milliseconds, respectively, and in those maintaining SR (n = 12 or 67%) 166 ± 13 and 141 ± 13 milliseconds, respectively. Significant parameters to predict rAF were (1) the ratios of the p5AFCL to the left atrium (LA) sizes corrected to the size of aorta (AO) and (2) LA sizes corrected to the size of AO. Conclusions and Clinical Importance Before TVEC, assessment of LA size and atrial electrophysiologic characteristics might help to identify horses at increased risk for AF recurrence.